“Tatters, Bloom’s Cat, and Other Animals in Ulysses” - Margot Norris (Humanities, 2017)
Given how few animals appear in the stories of Dubliners and in A Portrait of the Artist as a Young Man, we may be surprised to find a dog and a cat playing small roles in the third and fourth chapters of Ulysses. Their appearance in adjacent episodes is neither coincidental nor entirely casual, however, if one takes a careful look at their presentations. The animals’ circumstances are very different. Stephen Dedalus has been walking along the strand at Sandymount, when he spots a dog running along the sand, followed by its owners, a man and a woman whom he assumes to be cocklepickers. In the next chapter, Leopold Bloom is preparing breakfast for his wife when he hears his cat meowing and pours her some milk in a small bowl. It is particularly worth looking at the narration of these two scenarios because the different human perceptions and responses to animals they present help us analyze the challenges of resisting animal anthropomorphizing and its implications for the limitations and boundaries of preserving the status of animal “otherness” in a work of fiction. Put differently, the narrative strategies in “Proteus” and “Calypso” manage to maintain animal identity as that of “actors” rather than “characters,” while demonstrating what is required to maintain this status for them. I will discuss these two animals, dog and cat, in the order in which they appear in Ulysses, as well as a number of other animals appearing later in the work.